Rights reclamation. - Bell, William L. (Philosophical Studies, 2024)
According to a rights forfeiture theory of punishment, liability to punishment hinges upon the notion that criminals forfeit their rights against hard treatment. In this paper, I assume the success of rights forfeiture theory in establishing the permissibility of punishment but aim to develop the view by considering how forfeited rights might be reclaimed. Built into the very notion of proportionate punishment is the idea that forfeited rights can be recovered. The interesting question is whether punishment is the sole means for reclaiming forfeited rights. I argue for a pluralistic theory of rights reclamation, according to which, there are multiple ways by which a wrongdoer can recapture her forfeited rights. In particular, I argue that offering remorseful compensation is a valid means by which a wrongdoer might partially, or fully, reclaim her right against punishment.